A review of canola meal as an alternative feed ingredient for ducks - Wickramasuriya, Samiru Sudharaka (J Anim Sci Technol, 2015)
This review provides an overview of the published data on the canola meal and its suitability for duck as an alternative plant-origin protein source to soybean meal. Canola meal is a legume origin protein source containing comparable amino acid profile to soybean meal and rich in essential minerals and vitamins. Nonetheless, it is known to contain less in energy content than soybean meal. Factors like field conditions and processing methods creates compositional variations among canola meal. Presence of anti-nutritional factors such as phenolic substances, phytate and glucosinolates which are known to reduce growth performance in livestock animals, are the major drawbacks for canola meal to be a competitive plant-origin protein source in the feed industry. This review is focused to address i) nutritional characteristics and feeding value of canola meal for ducks and ii) impacts of feeding canola meal on performances of ducks.